2013
DOI: 10.1155/2013/764239
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Structure of Fish Collagen Nanofibers Influenced Cell Growth

Abstract: Electrospinning is highlighted in biomaterials field. The structures of nanofibers depend on various parameters, which are related closely to the bioactivity of biomaterials. The aim of this research is to analyze the structure of fish collagen nanofibers and to propose the new criterion for cell growth. This paper focused on the flow rate of solvent during the electrospinning. Through the cell culture, the relationship of the structure and cell growth is investigated. The results obtained in this study provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Interestingly, they also found that higher collagen concentration (at least 20%) was needed when acetic acid was used as the solvent to prepare the spinning solution. Fish collagen electrospinning also has been reported by other groups and the produced nanofibers were found to support cell biological activities [76][77][78].…”
Section: Effects Of Collagen Sources On Electrospun Collagen Nanofiberssupporting
confidence: 61%
“…Interestingly, they also found that higher collagen concentration (at least 20%) was needed when acetic acid was used as the solvent to prepare the spinning solution. Fish collagen electrospinning also has been reported by other groups and the produced nanofibers were found to support cell biological activities [76][77][78].…”
Section: Effects Of Collagen Sources On Electrospun Collagen Nanofiberssupporting
confidence: 61%
“…Its pore size was about 100-300 m, and its porosity was about 80%. Cellular activities were affected by chemical composition, conformation, porosity, and hydrophobicity of matrix [25]. The osteogenesis ability of nHAC/PLA composites were confirmed by osteoblasts culture and animal model tests [9].…”
Section: Discussionmentioning
confidence: 92%
“…4,[7][8][9] Scientists from Nanyang Technological University (NTU) in Singapore have demonstrated that collagen derived from fish scales is highly effective across a variety of biomedical applications such as wound healing. 10 Research conducted by Zhou et al (2013), strongly suggests that fish scales containing collagen can increase blood vessel and lymph formation, thereby promoting tissue repair and regeneration. 11 However, the findings of these studies suggest that the viability of the scales and thorns of Gurami and Kuniran fish remains unproven.…”
Section: Introductionmentioning
confidence: 99%
“…10 Research conducted by Zhou et al (2013), strongly suggests that fish scales containing collagen can increase blood vessel and lymph formation, thereby promoting tissue repair and regeneration. 11 However, the findings of these studies suggest that the viability of the scales and thorns of Gurami and Kuniran fish remains unproven. It is known that Gurami (fresh water) and Kuniran (salt water) are the types of fish most frequently consumed by the population of Jember, East Java, Indonesia.…”
Section: Introductionmentioning
confidence: 99%